Implementasi Model PAIKEM GEMBROT dalam Pembelajaran PAIBP pada Kelas II dan V di SDN 06 Batang Anai Kabupaten Padang Pariaman - Yanti, Fitri; Satria, Rengga (AS-SABIQUN, 2023)
This study aims to determine the planning, implementation, and evaluation of the GEMBROT PAIKEM model in PAIBP learning in class II and class V. This research is a qualitative descriptive research method with a case study type of method. Informants in this study were PAIBP teachers and school principals with data collection techniques namely observation, interviews, and documentation, while data analysis techniques used data collection, data reduction, data presentation, and drawing conclusions and verification. Based on the research results, it was found that the implementation of the PAIKEM GEMBROT model in PAIBP learning in grades II and V was divided into three stages, namely preliminary activities, core activities, and closing activities. Planning for the PAIKEM GEMBROT model in PAIBP learning in grades II and V is carried out by determining the next material which is guided by the syllabus, PROTA, PROMES, daily journals, then determining learning objectives, KD, achievement indicators, so that it becomes a lesson plan. Evaluation of the GEMBROT PAIKEM model in PAIBP learning in grades II and V is divided into three assessments, namely knowledge (cognitive), attitude (affective), and skills (psychomotor).